PENGARUH KECEMASAN PANDEMI COVID-19 TERHADAP PENGELUARAN ASI IBU MENYUSUI DI RUMAH SEHAT BUNDAATHAHIRA BANTUL - Pri Hastuti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2021)
Breast milk is the fluid secreted by the breast glands, which is the best nutritious and high-energy milk produced since pregnancy. One of the factors for failure in the breastfeeding process is due to the influence of psychological factors, namely the stressful emotional state of the mother. The aim of the study: The author wants to prove the effect of the anxiety of the COVID-19 pandemic on breastfeeding for breastfeeding mothers in ATHAHIRA's Mother's Healthy Home. Research design: with a cross section method of 30 people with nonprobability sampling technique and the instrument used in the form of a questionnaire. The results of the study: There was an effect of Covid-19 pandemic anxiety on post partum maternal breastfeeding (p value: 0.000 α: 0.05).